PHYSICO-CHEMICAL AND MICROBIOLOGICAL CHARACTERISTICS OF DEAD BIRD AND LITTER COMPOST DURING WINTER SEASON - M. K. N. Bukhari; S. Mehmood; A. Mahmud; A. Khalique; K. Javed; M. Nadeem; J. Hussain; M. T. Khan; M. S. Shaheen (Journal of Animal and Plant Sciences, 2017)
An exploratory study was conducted to evaluate the physico-chemical and microbiological characteristics of dead poultry and litter compost during different stages of composting in winter season. The present study was conducted under completely randomized design (CRD) by repeating the experimental trial for three times. For this purpose, three compost bins were loaded with organic waste comprising dead poultry and litter by following the internationally accepted standard method of bin filling. Sampling was done at the end of each phase to record the data for physico-chemical, mineral and microbiological parameters. The data were analyzed by using ANOVA technique under CRD. The results indicated higher maximum temperature, maximum moisture, and crude protein in primary phase, average temperature in secondary phase, dry matter, ash, calcium, phosphorus, and potassium content in curing phase of composting. However, nitrogen content, C:N ratio and bacterial count were significantly (P ≤ 0.05) reduced during curing phase of composting. It may be stated that composting technology is an environmentally safe method of dead birds’ disposal that can be used to convert organic waste into useful organic fertilizer.
Keywords: physico-chemical characteristic; microbiology; compost; winter season